2004
DOI: 10.1016/s0378-1097(03)00921-2
|View full text |Cite
|
Sign up to set email alerts
|

MprF-mediated biosynthesis of lysylphosphatidylglycerol, an important determinant in staphylococcal defensin resistance

Abstract: Frequently bacteria are exposed to membrane-damaging cationic antimicrobial molecules (CAMs) produced by the host's immune system (defensins, cathelicidins) or by competing microorganisms (bacteriocins). Staphylococcus aureus achieves CAM resistance by modifying anionic phosphatidylglycerol with positively charged L-lysine, resulting in repulsion of the peptides. Inactivation of the novel S. aureus gene, mprF, which is found in many bacterial pathogens, has resulted in the loss of lysylphosphatidylglycerol (L-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
142
3

Year Published

2008
2008
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 167 publications
(148 citation statements)
references
References 24 publications
3
142
3
Order By: Relevance
“…It has recently been shown that increasing levels of Lys-PG and other lysylated phospholipids promote the rigidification and stabilisation of bacterial membranes through the reduction of electrostatic repulsion between anionic lipid head-groups, thereby inhibiting the ability of AMPs to penetrate these membranes 35,36 . Moreover, it is generally accepted that a contribution to the protective mechanism provided by Lys-PG derives from a 'charge effect' whereby the positively charged head-group carried by the lipid is able to reduce the net negative charge of host bacterial membranes thus inhibiting the binding of cationic AMPs to these membranes 27,28,31,[33][34][35][36][37][38] . It therefore seems likely that the contribution made by 'charge effects' to this protective mechanism is further enhanced by low pH given that the Lys-PG head-group is predominantly cationic under acid conditions but becomes more zwitterionic in character as pH is increased 29,93 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It has recently been shown that increasing levels of Lys-PG and other lysylated phospholipids promote the rigidification and stabilisation of bacterial membranes through the reduction of electrostatic repulsion between anionic lipid head-groups, thereby inhibiting the ability of AMPs to penetrate these membranes 35,36 . Moreover, it is generally accepted that a contribution to the protective mechanism provided by Lys-PG derives from a 'charge effect' whereby the positively charged head-group carried by the lipid is able to reduce the net negative charge of host bacterial membranes thus inhibiting the binding of cationic AMPs to these membranes 27,28,31,[33][34][35][36][37][38] . It therefore seems likely that the contribution made by 'charge effects' to this protective mechanism is further enhanced by low pH given that the Lys-PG head-group is predominantly cationic under acid conditions but becomes more zwitterionic in character as pH is increased 29,93 .…”
Section: Discussionmentioning
confidence: 99%
“…According to this mechanism of resistance, cationic AMPs activate a sensor histidine kinase (ApsS) of the ApsSR (GraSR) regulon, which leads to the up-regulated expression of the virulence factor mprF. The protein product of this gene, mprF, is a Lys-PG synthase that catalyses the transfer of lysine from lysyl-tRNA to the PG head-group and flipping of the resulting Lys-PG to the outer leaflet of the S. aureus CM 23,[31][32][33][34] . The presence of the lipid in the CM of S.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The reaction is catalysed by the membrane protein MprF, which also supplies the translocase activity that subsequently transfers lysyl-PG from the inner to the outer membrane leaflet. 92 The abundance of lysyl-PG in bacterial membranes correlates with resistance to both cationic antimicrobial peptides 93 and daptomycin. Gainof-function mutations in the mprF gene cause increased lysyl-PG levels, decreased PG levels, and daptomycin resistance in Staphylococcus aureus (see reference 94 and citations therein).…”
Section: Lysyl-phosphatidylglycerolmentioning
confidence: 99%
“…While the physiological significance of the MprF pathway has recently been explored, and qualitative in vitro TLC assays were set up using radiolabeled Lys (11), there is to date no convenient in vitro assay to quantitatively monitor the Lys-tRNA Lys PG transferase activity. Here we report general methods to express and obtain an enriched cellular fraction containing active MprF.…”
Section: Introductionmentioning
confidence: 99%